1984
DOI: 10.21273/hortsci.19.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Survival, Growth, and Yield of Peach Trees as Affected by Rootstocks

Abstract: Effects of 8 peach seedling rootstocks on tree growth, survival, and fruit yield of ‘Redhaven’ and ‘Loring’ peach scion cultivars were tested in Alabama, Arkansas, Georgia, North Carolina, and South Carolina. Lovell seedling rootstock was a standard for comparison. Six years of data indicated that Siberian C was not an acceptable rootstock because tree survival and fruit yield were low. Halford was equivalent to Lovell for tree growth, fruit yield, and survival. Fruit size was unaffected by rootstock. Nemaguar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 13 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…Tree loss due to cold injury, bacterial canker (Pseudomonas syringae pv syringae van Hall), or both, were major causes of death in the cooperative peach rootstock trial conducted in the southeast (5). Trees on Siberian C generally exhibited the greatest amount of tree loss and could not be recommended in the region; however, losses of the other seven rootstocks varied dramatically from site to site.…”
Section: Relative Tree Sizementioning
confidence: 99%
See 1 more Smart Citation
“…Tree loss due to cold injury, bacterial canker (Pseudomonas syringae pv syringae van Hall), or both, were major causes of death in the cooperative peach rootstock trial conducted in the southeast (5). Trees on Siberian C generally exhibited the greatest amount of tree loss and could not be recommended in the region; however, losses of the other seven rootstocks varied dramatically from site to site.…”
Section: Relative Tree Sizementioning
confidence: 99%
“…Commercially available rootstocks for peach tend to be from seedling sources and do not offer the wide range of tree sizes present with apple (43). A regional cooperative study comparing eight Prunus rootstocks showed only a 10% difference in tree size between the largest and smallest rootstock/scion combinations (5). Layne (36), in a recent review, discussed in detail the capabilities of the rootstocks currently being used for peach around the world and reported that rootstocks were available ranging from about 50% dwarfing to about a 25% increase in tree size.…”
mentioning
confidence: 99%
“…A rating system based on a scale from 1 to 9 (0 = no data) reported by Fogle (3) for evaluating fruit tree per formance, seems to be precise, adequately detailed, and logical for use with modem data handling systems. In practice, accurate estimation of tree damage status at a very early stage of injury and good correlation with ultimate tree survival have been possi ble through the trunk cambial browning (TCB) and bacterial canker (BCR) ratings on a 1 to 9 scale (2,7,8). This article provides de scriptive details of key stages of damage se verity and portrays these stages pictorially for further clarity (Table 1, Fig.…”
Section: Received For Publicationmentioning
confidence: 99%